2017
DOI: 10.1002/berj.3296
|View full text |Cite
|
Sign up to set email alerts
|

Brokering to support participation of disadvantaged families in early childhood education

Abstract: This paper discusses findings from an evaluation of the New Zealand Ministry of Education's Early Childhood Education (ECE) Participation Programme that targeted local areas where there are high numbers of children starting school who have not participated in ECE. The aim of the programme is to increase participation of these low‐income ‘priority’ children in ‘quality’ ECE. In this paper, two policy initiatives and features that supported participation in ECE are analysed. Engaging Priority Families (EPF) invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Finally, some providers may be better placed than others to communicate the existence of free places and their potential benefits, particularly to low‐income families. Sure Start children's centres offer wider services for young children from birth onwards, including health clinics and ‘stay‐and‐play’ sessions, and also have a specific remit of outreach to disadvantaged groups, which evidence indicates can increase take‐up (Mitchell & Meagher‐Lundberg, ). Parents accessing Sure Start services for their babies and toddlers are likely to get to learn what is available when their child turns three.…”
Section: The Free Entitlement To Early Education: How It Workmentioning
confidence: 99%
“…Finally, some providers may be better placed than others to communicate the existence of free places and their potential benefits, particularly to low‐income families. Sure Start children's centres offer wider services for young children from birth onwards, including health clinics and ‘stay‐and‐play’ sessions, and also have a specific remit of outreach to disadvantaged groups, which evidence indicates can increase take‐up (Mitchell & Meagher‐Lundberg, ). Parents accessing Sure Start services for their babies and toddlers are likely to get to learn what is available when their child turns three.…”
Section: The Free Entitlement To Early Education: How It Workmentioning
confidence: 99%
“…Similar to previous studies, the access of ECE was still significantly tied to children's socio-economic background (Bridges, Fuller, Rumberger, & Tran, 2004). Despite the fact that the overall participation rate was still below the government's official target, students from higher social status backgrounds had a significantly higher enrollment percentage than their peers from less privileged communities (Mitchell & Meagher-Lundberg, 2017;Skattebol, 2016). A previous `study found that ECE participation in formal or nonformal institutions was vary considerably by region and wealth in which the rate for the richest is almost four times higher than the poorest (National Development Planning Agency, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Earlier research has suggested that access to ECEC consists of affordability, availability, amenability and acceptability of ECEC services (see e.g., Vandenbroeck & Lazzari, 2014). Acceptability of the services has been investigated from the point of view of parents (Mitchell & Meagher-Lundberg, 2017;Vandenbroeck et al, 2008). Our findings suggest that even though ECEC policies at national level can be seen as universal supporting affordability, availability and amenability of the ECEC services, we need to pay attention to how local enactments of ECEC policies might construct barriers related to the acceptability of the use of services.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the constructed distinction found in this study between children and families 'of concern' and 'not of concern' implies a targeted rather than a universal approach in rationalising access to ECEC services. According to earlier research, parents' conceptions of the purpose of ECEC services and the target group for whom the services are intended matters in their decisions regarding childcare (Mitchell & Meagher-Lundberg, 2017;Vandenbroeck et al, 2008). The fact that the use of ECEC services might be seen as culturally inappropriate or marking the family as being 'of concern' can create a barrier to parents positioned as being 'at home' to applying for an ECEC place for their child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation